Broadening the sunlight response region with carbon dot sensitized TiO2 as a support for a Pt catalyst in the methanol oxidation reaction. Issue 16 (26th July 2018) - Bora, Anindita; Mohan, Kiranjyoti; Doley, Simanta; Goswami, Prayashi; Dolui, Swapan Kumar
Abstract : Carbon dots with upconversion properties harness unused visible light and act as sensitizers for a TiO2 supported Pt catalyst in MOR. Abstract : TiO2 is a celebrated photo-catalyst for methanol oxidation reaction (MOR). However, its modification is necessitated by a narrow light response region and swift recombination of electrons and holes. Incorporating carbon dots (CDs) with TiO2 can broaden the light response range, while a composite of TiO2 with Pt can significantly enhance the catalytic performance and also suppress the electron–hole recombination process. Herein, we report the structural, optical and electrochemical evaluation of a new photo-electrocatalyst – platinized TiO2 sensitized by CDs – through a series of systematic studies. Reasonably, by combining both photo-catalytic and electro-catalytic mechanisms, the ternary composite catalyst (Pt/CD/TiO2 ) under irradiation shows better performance in the MOR in terms of the forward peak current density value of 2.5 mA cm −2, which exceeds that obtained without illumination by 24%. The performance enhancement can be attributed to the unique upconversion properties of CDs that allow the utilization of the visible solar range, which is otherwise restricted in case only TiO2 is present.